DINAMIKA PSIKOLOGIS KETIDAKJUJURAN SANTRI DAN PENANGANANNYA (STUDI KASUS DI PESANTREN SULTAN HASANUDIN) - Alsiqra, Alimul Ashar; Umar, Nur Fadhilah; Aswar, Aswar (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
This study explores the psychological dynamics underlying dishonest behavior among Islamic boarding school students (santri) and the handling strategies applied within the Sultan Hasanuddin Islamic Boarding School environment. The research aims to (1) describe the forms of dishonesty exhibited by a student identified as GR, (2) identify both internal and external factors contributing to such behavior, and (3) explain the counseling interventions implemented to modify the dishonest tendencies. This study employs a qualitative approach with a clinical case study design. The research subject is a student who frequently engages in deceptive behavior in various school contexts. Data were collected through in-depth interviews, structured observations, and documentation analysis, then processed through data reduction, presentation, and interpretative conclusion drawing. The findings reveal that GR’s dishonesty appears in lying to teachers, manipulating information to avoid punishment, and concealing mistakes when reprimanded. Internal factors include excessive anxiety about sanctions, feelings of shame and inferiority, and cognitive distortions perceiving honesty as a threat. External factors consist of the strict boarding school regulations, high expectations from supervisors, and peer influence encouraging concealment of mistakes. The intervention applied was counseling based on the Cognitive Behavioral Therapy (CBT) approach using the cognitive restructuring technique. The intervention focused on building a counselor-client relationship, exploring the motives behind lies, practicing gradual behavioral changes, and conducting continuous evaluations. The results indicate increased self-awareness, greater courage to be honest despite risks, and a strengthened commitment to reducing dishonesty as a maladaptive self-protection mechanism.